Efektivitas penggunaan aplikasi whatsapp sebagai media belajar bahasa indonesia di rumah di kelas V sekolah dasar - Dinda Kristiningrum; Sukarno Sukarno; Muhammad Ismail Sriyanto (Didaktika Dwija Indria, 2022)
This researchaimsto provide an overview of the effectiveness of using the WhatsApp application as a media for learning the Indonesian language at home. This research includes qualitative research with descriptivemethods and phenomenological approaches. Teachers and students of class V SD Negeri Pajang IV Surakarta that in total 27 students, were the subject of the study. Data collection techniques were used interviews, questionnaires, and documentation. The data validity test technique was used triangulation techniques. The data analysis technique was based on Miles and Huberman's interactive analysis technique through data reduction, data presentation, and drawing conclusions. The results showed that the use of the WhatsApp application as a media for learning the Indonesian language at home could be categorized as effective. Of the 11 descriptors 9 descriptors of media effectiveness have been achieved in the use of the WhatsApp application as a media for Indonesian language learning.